2018
DOI: 10.4103/jpbs.jpbs_234_17
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of health-care professionals toward adverse drug reactions reporting at King Saud Medical City

Abstract: Background:Health-care professionals across the globe are obligated to report adverse drug reactions (ADRs). The knowledge of ADRs and attitude of health-care professionals toward ADRs reporting is vital for patient safety. This study intends to investigate the knowledge of ADRs and attitude of health-care professionals toward ADRs reporting.Materials and Methods:A cross-sectional study using an anonymous questionnaire was conducted over a period of 3 months (September 2016 to November 2016) at King Saud Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Few of the included studies had evaluated the perception of HCPs toward ADR reporting and most of these studies evaluated the perception by asking whether the HCPs think that reporting ADR will positively impact the healthcare (HC) system, patient care, improves the quality of life, or contributes to drug safety. The perception of HCPs toward this question ranged from 46.53% to 100% [14,18,20,26,29,30,[34][35][36]39]. The studies also show that HCPs think that it is important to report ADR and their perception was from 11.34% to 97% [13,17,19,21,23,24,31,34,36,38], and they believe it should be compulsory for HCPs to report ADR reaction with a perception ranged from 12% to 93.80% [13,18,19,25,26,30,31,35,39].…”
Section: Adverse Drug Reaction Reporting Perceptionmentioning
confidence: 91%
See 3 more Smart Citations
“…Few of the included studies had evaluated the perception of HCPs toward ADR reporting and most of these studies evaluated the perception by asking whether the HCPs think that reporting ADR will positively impact the healthcare (HC) system, patient care, improves the quality of life, or contributes to drug safety. The perception of HCPs toward this question ranged from 46.53% to 100% [14,18,20,26,29,30,[34][35][36]39]. The studies also show that HCPs think that it is important to report ADR and their perception was from 11.34% to 97% [13,17,19,21,23,24,31,34,36,38], and they believe it should be compulsory for HCPs to report ADR reaction with a perception ranged from 12% to 93.80% [13,18,19,25,26,30,31,35,39].…”
Section: Adverse Drug Reaction Reporting Perceptionmentioning
confidence: 91%
“…The characteristics of the included studies are displayed in Table 1. Ten studies included HCPs namely: physicians, dentists, pharmacists, pharmacy technicians and nurses [13,16,17,21,[23][24][25][26][27]39], 7 other studies focused on the KAP on community pharmacists [14,15,19,30,5,36,38], 3 focused on physicians [18,22,33], 3 focused on hospital pharmacists [20,31,4], 2 focused on hospital and community pharmacists [28,37], 1 focused on physicians and dentists [33], and 1 focused on hospital pharmacists [32].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…If they have confidence in their ability to diagnose, manage, and prevent such reactions, they will more likely to identify and report important ADRs. [12][13][14][15][16] Several studies, however, reported that there is under-reporting of ADR globally. The studies also showed the lack of adequate knowledge, attitude, and practice (KAP) about PV activities and ADR reporting is among the main reasons for underreporting of ADRs.…”
Section: Introductionmentioning
confidence: 99%